Association between physical activity and motor skills and coordination in Portuguese children. - Luís Oliveira Lopes; Vítor Pires Lopes; Rute Santos; Beatriz Pereira (Universidade Federal de Santa Catarina, 2011)
Nowadays, there is growing evidence in literature that Health benefits from regular physical activity (PA). The variance in PA among children is caused by a number of factors including their motor abilities and coordination. The aim of the study was to analyse the relation between usual PA and gross motor abilities and motor coordination in children aged 6 to 7 years. The sample comprised 21 children, aged in average 6,38±0,50 years. Physical activity was accessed by accelerometry, gross motor abilities by using the Test of Gross Motor Development (TGMD-2) and motor coordination by using the Körperkoordination Test für Kinder (KTK). Subjects met the international recommendations for daily PA; in motor coordination 47,6% of children met normal coordination, nobody reach good or very good coordination, the majority (52,4%) revelled disturbances or insufficiencies of coordination; in locomotion TGMD-2 76,2% of the children met percentile 50 or superior (P50), in object control TGMD-2 28,6% of the children reach P50 or superior, in total TGMD-2 38,1% of the children met P50 or superior. PA was positively correlated with TGMD-2 object control. Low performance attributed to the children in TGMD-2 and KTK tests could be an indicative of insufficient in the development of coordination and gross motor abilities; therefore we believe that this kind of intervention should be targeted at school children mainly in Physical Education classes.